Demographic dynamics, labor force participation and household asset accumulation case of Japan - Ando, Albert; Moro, Andrea (1995)
A dynamic model of the demographic structure of Japan is summarized. It is capable of tracing the dynamic development of the Japanese population, including the distribution of families by age, sex, and marital status of the head, as well as by the number and age of children and other dependents. This model is combined with a specification of the processes generating family income and consumption, and then used to generate the pattern of aggregate income, saving and asset accumulation for the period 1985-2090 under alternative fertility assumptions. The results suggest that the saving-income ratio for Japan will increase slightly in the immediate future as the number of children per family declines sharply, and then fall moderately as the proportion of older persons in the population increases. Quantitative results depend critically on the labor force participation rate of older persons and on the probability of older persons merging into younger households. However, unless some major changes in Japanese saving behavior take place, our analysis suggests that Japan will have an unusually high net worth-income ratio as its population stabilizes or begins to decline.
Keywords: Income -- Japan; Labor supply -- Japan; Japan -- Population